Connections among physical activity, motivation, and depressive symptoms in adolescent girls. (August 2020) - Cecchini, Jose A; Fernandez-Rio, Javier; Mendez-Gimenez, Antonio; Sanchez-Martinez, Beatriz
Adolescence can be a difficult period of life characterised, among many other things, by a significant increase in depressive symptoms among girls. Recent studies have suggested that sedentary habits and self-determined motivation can be associated with depressive symptoms. The main goal of the present study was to examine the associations between physical activity levels, sedentary behaviours, and self-determined motivation and depressive symptoms in girls during adolescence. A total of 714 adolescent girls (16.53 ± 1.01 years) agreed to participate in the study. They completed a questionnaire including the scale of depressive symptoms, the International Physical Activity Questionnaire, and the Situational Motivation Scale. Participants' smoking habits and body mass index were also assessed. Results showed that those adolescents who performed physical activity of moderate (odds ratio (OR): 0.55; 95% confidence interval (CI): 0.31, 0.99) or high intensity level (OR: 0.22; 95% CI: 0.10, 0.21) had a significantly lower probability of suffering from depressive symptoms. Accordingly, the most sedentary group had a higher probability of suffering from depressive symptoms (OR: 4.90; 95% CI: 2.00, 11.54). Vigorous self-determined motivation was also a significant predictor of the lowest levels of depressive symptoms. In conclusion, results seemed to indicate that educators should promote the most self-determined types of motivation and physical activity habits in their students if they want to help prevent depressive symptoms.